Investigating the entrepreneurial self-efficacy in the relationship between entrepreneurship education and student’s self-employment intentions: an empirical analysis from Malaysia - Hassan, Mohammad Mujaheed; Haris Fadzilah, Asmaul Husna; Ismail, Mohammad Naim; Hassan, Muhamad Hafiz; Abdullah, Mohammad (Telematique, 2024)
The rise of self-employment is influenced by a number of personal and environmental factors among which we may distinguish the factors linked to education in entrepreneurship as well as personal characteristics. Given this aspect, the purpose of this paper is to investigate the main factors influencing students’ self-employment intentions, paying particular attention to their entre- preneurial self-efficacy. Additionally, the paper aims to explore the effect of entrepreneurial self- efficacy on the relationship between entrepreneurship education and self-employment intention. We conducted a study where results were based on the outcomes of a survey among Malaysian public university students (N = 388). Our four main hypotheses were tested through multiple re- gression analysis. The findings highlighted that the students with an entrepreneurial self-efficacy reported a positive relationship with self-employment intention. The variables that positively influ- enced the self-employment intentions of the students were entrepreneurial self-efficacy and entre- preneurship education. Furthermore, this entrepreneurial self- efficacy positively mediates the rela- tionship between entrepreneurship education and self-employment intention. For this reason, em- phasis should be placed on both formal and informal entrepreneurial education, which will increase the propensity of young people to choose an entrepreneurial career.